2000
DOI: 10.1029/1999jd901194
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and energetics of the cloudy boundary layer in simulations of off‐ice flow in the marginal ice zone

Abstract: Abstract. The case under congideration occurred on March 4, 1993, and was observed as part of the Radiation and Eddy Flux Experiment (REFLEX II) 1993 observational campaign northwest of Spitsbergen. The off-ice flow on this day brought very cold surface air temperatures (-35øC) over a relatively warm ocean surface. The resultant latent and sensible surface heat fluxes produced intense convection and a thermal internal boundary layer (TIBL) which deepened with distance from the ice edge. Two-dimensional cloudre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…Rao and Agee [1996] found that inclusion of snow processes in the simulation produced fundamentally different boundary layer turbulence and convective organization. Olsson and Harrington [2000] found that inclusion of mixed-phase microphysics had a large impact on boundary layer depth and structure. Icephase precipitation processes rapidly depleted the boundary layer of condensate, and the less humid boundary layer was able to maintain a larger surface latent heat flux and continuously extract heat through condensation and deposition.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Rao and Agee [1996] found that inclusion of snow processes in the simulation produced fundamentally different boundary layer turbulence and convective organization. Olsson and Harrington [2000] found that inclusion of mixed-phase microphysics had a large impact on boundary layer depth and structure. Icephase precipitation processes rapidly depleted the boundary layer of condensate, and the less humid boundary layer was able to maintain a larger surface latent heat flux and continuously extract heat through condensation and deposition.…”
Section: Introductionmentioning
confidence: 97%
“…Numerous simulations of cold air outbreaks have also been conducted [e.g., Chlond, 1992;Bakan et al, 1995;Rao and Agee, 1996;Olsson and Harrington, 2000;Brummer and Pohlmann, 2000;Flamant et al, 2001;Pagowski and Moore, 2001] as well as simulations of cloud plumes from the cooling ponds [e.g., Shannon and Everett, 1978;Leahey et al, 1979;Yamada, 1979;Khvorostyanov, 1991].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Herman and Goody (1976) suggest that the stationarity of the synoptic flow in the central Arctic acts to minimize mechanisms of stratus dissipation. Curry (1986) asserts that surface fluxes are not responsible for Arctic stratus formation under the strongly stable conditions present in winter and early spring, but this may not be the case for late spring through October when open ocean is a significant factor (Pinto and Curry 1995;Olsson and Harrington 2000). Although many details of these cloud formation and persistence processes are not well understood, cloud-scale vertical motions are a key feature of mixed-phase clouds that affect their evolution and support their extended lifetimes (e.g., Rauber and Tokay 1991).…”
Section: Introductionmentioning
confidence: 99%
“…They found that it was essential for an accurate modelling of the specifi c humidity fi eld to account for deposition growth of cloud ice. Olsson and Harrington ( 2000 ) conclude from their sensitivity study with a high-resolution 2D model that the amount of cloud condensate strongly infl uences the ABL structure due to radiation effects. …”
mentioning
confidence: 99%